Thermal Comfort Attainment by Personal Vortex Tube Cooling Device - Mohd Hazwan, Yusof; Amirul Nawaf, Esa; Muhammad Fadhli, Suhaimi (Springer Science and Business Media Deutschland GmbH, 2023)
A vortex tube is a small cooling device that uses compressed gas to produce cold flow with a temperature as low as −30 °C. In industries, this cold flow is used to reduce the temperature of mechanical parts of machines, environmental chambers, and electrical components.